Comoros : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
The statistical data on gross domestic product, cost structure of vanilla exports, production of meat, fish, and dairy products, consumer price index, and consolidated government financial operations of Comoros have been presented in this paper. The wage bill developments, consolidated net statement of public enterprises, monetary survey, summary statement of the central bank, volume and value of principal exports, geographical distribution of trade, external debt payments, arrears by creditors, and related economic indices have been included in the statistical data.